Drivers of coral reconstructed salinity in the South China Sea and Maritime Continent: the influence of the 1976 Indo‐Pacific climate shift - Kannad, Ankitha (2023)
The flow of Pacific water into the Indian Ocean via the South China Sea (SCS) and Maritime Continent (MC) plays an important role in the ocean thermohaline circulation providing the only low-latitude pathway for the inter-ocean exchange of heat and salt. The transport of the SCS and Indonesian throughflows is modulated by the East Asian monsoon and major climate modes associated with the Pacific and Indian Oceans. As an indicator of surface layer buoyancy, sea surface salinity (SSS) is critical to rates of exchange but instrumental records of SSS are short and sparse. Using empirical orthogonal functions, a synthesis of proxy-based reconstructions of SSS from coral δ18O is used to study the role of climate variability on long-term SSS behavior in the region. The leading mode of SSS variability in the boreal winter and summer responds to the influence of the 1976 Indo-Pacific climate shift. At multi-decadal timescales, only the East Asian monsoon and the Indian Ocean Dipole (IOD) retain their signal in winter and summer SSS after 1976. At higher frequencies, winter SSS shifts from having a strong East Asian monsoon signal to a more dominant impact of the IOD and the El Niño Southern Oscillation (ENSO) following the shift. In the summer, only a change in ENSO's influence on SSS variability is observed after 1976. The recent intensification and dominance of the IOD and ENSO in driving SSS variability in the SCS and MC may influence circulation in the regional throughflows and perhaps global thermohaline circulation.